TORK DAN PENGGUNAANNYA DALAM PERAWATAN ORTHODONTIK - Eky S. Soeria Soemantri; Endah Mardianti (Faculty of Dentistry, Universitas Indonesia, 2015)
To obtain a final occlusion, torque is needed to place the teeth in a precise labiolingual or buccolingual position. Biomechanically principles and arch manipulation is compulsory to produce torque movement. This paper discusses the technique to produce torque and its biomechanical principles. There are two kinds of torque, root torque and crown torque which can be done on anterior as well as posterior teeth. By holding the crown in its position while applying a moment of a force on the rest, root torque can be obtained. In root torque, the center of rotation is at the incisal edge or at the bracket with a 12:1 moment to force ratio. Torque can be produced by using rectangular wire or using torquing auxiliaries. Torque movement is frequently needed in orthodontic treatment, which needs a thorough understanding a biomechanical principles.